2009
DOI: 10.1055/s-0029-1214604
|View full text |Cite
|
Sign up to set email alerts
|

In vivo diagnosis of acute intestinal graft-versus-host disease by confocal endomicroscopy

Abstract: CEM improves rapid diagnosis of acute intestinal GvHD with high accuracy while performing endoscopy. Platelet transfusions and unnecessary biopsy acquisition can be avoided once acute intestinal GvHD has been diagnosed in vivo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
38
1
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(42 citation statements)
references
References 18 publications
1
38
1
2
Order By: Relevance
“…C onfocal laser endomicroscopy (CLE) is a novel technique for imaging live cells during endoscopy [1][2][3][4][5][6][7][8]. Upon systemic administration of the dye fluorescein, CLE can be performed in vivo during ongoing endoscopy and permits real-time subsurface imaging of cellular and subcellular structures in the mucosa.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…C onfocal laser endomicroscopy (CLE) is a novel technique for imaging live cells during endoscopy [1][2][3][4][5][6][7][8]. Upon systemic administration of the dye fluorescein, CLE can be performed in vivo during ongoing endoscopy and permits real-time subsurface imaging of cellular and subcellular structures in the mucosa.…”
mentioning
confidence: 99%
“…It was found that high-quality in vivo imaging could be performed and CLE was utilised for rapid diagnosis and for the targeting of biopsies. In addition, CLE was shown to predict neoplasia in the stomach, oesophagus and colon with high accuracy [1][2][3][4][5][6][7][8].…”
mentioning
confidence: 99%
“…In a recent trial, eCLE was able to diagnose and to grade GvHD during ongoing endoscopy with high accuracy based on the presence of inflammation, and epithelial apoptosis could be documented for diagnosis [56]. CLE has not been extensively studied in infectious colitis, but a case report has shown visualization of intestinal spirochaetosis by CLE [57].…”
Section: Endomicroscopy In Colitismentioning
confidence: 99%
“…Therefore, for grades 2-4 there was a strong correlation between endomicrosopy and conventional histology with a sensitivity of 74% and specificity of 100%. 76 The early promise of CLE in GVHD may provide a real-time diagnosis of GVHD to be made allowing intensification of immunosuppression or at least targeting of areas of active disease with fewer biopsies and reduced risk of biopsy related complications.…”
Section: Graft-versus-host Disease (Gvhd)mentioning
confidence: 99%